TRAINING TO IMPROVE THE ABILITY TO MANAGE FINANCES BASED ON SIMPLE CASH FLOW AND HALAL CERTIFICATE ASSISTANCE THROUGH SELF-DECLARATION FOR UMKM ASSISTED BY THE COOPERATIVE AND SME OFFICE OF SOUTH SUMATRA PROVINCE. - Sri Delasmi Jayanti; Aziz Septiatin; Yusiresita Pajaria; Vera Amalia (CV. Doki Course and Training, 2023)
Based on the religious life report from 2013, Indonesia is one of the world's largest Muslim countries, home to about 237,641,326 people. Some of its food imports come from various non-Muslim nations. As a result, the halal certification and labeling procedure for goods that are in use worries some Muslims. And this research in this study explains how to see and distinguish how important the halal label is on product packaging. The participants in this activity were 40 MSME business actors assisted by the Cooperative and UKM Office of South Sumatra Province, at the Entrepreneurship Laboratory of the Faculty of Economics and Islamic Business, UIN Raden Fatah Palembang Jakabaring Campus